2000
DOI: 10.1046/j.1460-9568.2000.01027.x
|View full text |Cite
|
Sign up to set email alerts
|

The human eye expresses high levels of CB1 cannabinoid receptor mRNA and protein

Abstract: We used reverse transcriptase polymerase chain reaction to detect the expression of the central and peripheral cannabinoid receptors (CB1 and CB2, respectively) mRNA, and Western blotting to show the presence of the CB1 protein in subregions of the human eye. CB2 mRNA transcripts were undetectable, while levels of CB1 mRNA were significantly expressed in the human retina (25.8 +/- 2.46%), ciliary body (210 +/- 11.55%) and iris (62.7 +/- 5.94%) when compared with those of the normalizing reference gene beta2 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 31 publications
6
53
0
Order By: Relevance
“…This study demonstrates that endogenously expressed CB 1 receptors in ocular hTM cells are capable of pleiotropy in signal transduction in an agonist-dependent manner by coupling to either G q/11 or G i/o to increase [Ca 2 þ ] i and activate ERK1/2. Cannabinoid receptors and their endogenous ligands, anandamide/arachidonylethanolamide and 2-AG, are present in tissues of both the anterior and posterior chambers of the mammalian eye (Bisogno et al, 1999;Straiker et al, 1999;Lu et al, 2000;Porcella et al, 2000;Chen et al, 2005). This distribution suggests they may play an important role in a diverse array of ocular functions including IOP regulation (reviewed in Tomida et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study demonstrates that endogenously expressed CB 1 receptors in ocular hTM cells are capable of pleiotropy in signal transduction in an agonist-dependent manner by coupling to either G q/11 or G i/o to increase [Ca 2 þ ] i and activate ERK1/2. Cannabinoid receptors and their endogenous ligands, anandamide/arachidonylethanolamide and 2-AG, are present in tissues of both the anterior and posterior chambers of the mammalian eye (Bisogno et al, 1999;Straiker et al, 1999;Lu et al, 2000;Porcella et al, 2000;Chen et al, 2005). This distribution suggests they may play an important role in a diverse array of ocular functions including IOP regulation (reviewed in Tomida et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of CB 1 receptors in the tissues of both inflow and outflow pathways in the eye (Straiker et al, 1999;Porcella et al, 2000;Stamer et al, 2001) indicates that activation of CB 1 at multiple sites probably contributes to a net decrease in IOP. Consistent with this, changes in aqueous inflow (Chien et al, 2003) and outflow (Colasanti, 1990;Beilin et al, 2000) have been observed following cannabinoid administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cannabinoids act on G-protein-coupled receptors (CB1 and CB2). RT-PCR and in situ hybridization indicate the presence of both CB1 and CB2 receptors throughout the retina (Lu et al, 2000;Buckley et al, 1998;Porcella et al, 2000). CB1 receptor antibodies label many neurons in the retina, including rod and cone terminals (Straiker et al, 1999;Yazulla et al, 1999;Straiker and Sullivan, 2003).…”
Section: Cannabinoids-cannabinoidsmentioning
confidence: 99%
“…Among the GPCRs identified in the CBE are A3 adenosine (Mitchell et al, 1999;Avila et al, 2001) and cannabinoid 1 (CB1) receptors (Porcella et al, 1998;Straiker et al, 1999;Stamer et al, 2001). Agonists for these receptors have been reported to alter intraocular pressure (IOP) (Crosson, 1995(Crosson, , 2001Crosson & Petrovich, 1999;Pate et al, 1996;Tian et al, 1997;Porcella et al, 2000;2001;Song & Slowey, 2000;Avila et al, 2001).…”
Section: Introductionmentioning
confidence: 99%